PUBLIC COMMUNICATION BETWEEN MEDIA DISRUPTION AND PUBLIC LITERACY IN THE DIGITAL ERA - Suputra Widharma, I Gede; Kiriana, I Nyoman; Dewi Anggreni, A. A. Made (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
The digital era has brought fundamental changes in public communication practices, where interactions are no longer top-down but rather horizontal and participatory through various social media platforms. This study aims to analyze the dynamics of public communication in the digital era by highlighting emerging communication patterns, forms of digital media disruption, and public literacy strategies in responding to them. The research method used is descriptive qualitative with a literature study approach and analysis of digital communication phenomena in Indonesia. The results show that current public communication is characterized by real-time interactivity, the dominance of visual content, and digital community involvement. However, this phenomenon also presents challenges in the form of information overload, hoaxes, filter bubbles, and opinion polarization. The young age group (17–25 years) has the highest digital literacy rate (82%), while the elderly (60+) tends to have the lowest (45%). Social media (45%) and online public sites (15%) is the most favourite media. Public literacy strategies have proven crucial for improving critical thinking skills, strengthening media awareness, and mitigating the negative impacts of disruption. This study concludes that adaptive digital literacy is the main foundation for building healthy and sustainable public communication in the digital era.